A case of anti-BP230 antibody-positive bullous pemphigoid receiving DPP-4 inhibitor. Issue 1 (2nd January 2021) - Sawada, Kaori; Sawada, Tomoyo; Kobayashi, Tadahiro; Fujiki, Akiko; Matsushita, Takashi; Kawara, Shigeru; Izumi, Kentaro; Nishie, Wataru; Shimizu, Hiroshi; Takehara, Kazuhiko; Hamaguchi, Yasuhito
Abstract: Bullous pemphigoid (BP) is a cutaneous autoimmune blistering disorder. Recently, it has been reported that dipeptidyl peptidase-4 inhibitors (DPP4i) is associated with the development of BP (DPP4i-BP). Patients with DPP4i-BP have autoantibodies (autoAbs) preferentially targeting full-length BP180, but not the BP180NC16a domain. In this report, we described a case of anti-BP230 antibody (Ab)-positive BP receiving DPP4i. A 78-year-old male with a medical history of type 2 diabetes receiving vildagliptin at 100 mg daily for 38 months was referred to our hospital with itching blisters on his body and extremities. Skin biopsy showed subepidermal bulla with eosinophil infiltration. Direct immunofluorescence staining revealed a linear staining pattern with complement C3 and IgG at the subepidermal basement membrane zone. By laboratory testing, autoAbs against BP180NC16a and full-length BP180 were negative by enzyme-linked immunosorbent assay (ELISA); however, anti-BP230 Abs were positive by ELISA (index: 123.91). His HLA genotype was DQB1*04:01 and 05:01. Based on these results, we diagnosed the patient with anti-BP230 Abs-positive BP associated with DPP4i. To the best of our knowledge, this is the first case of DPP4i-BP with only anti-BP230 Abs. Further accumulation of DPP4i-BP cases is needed to clarify the relationship between overall features of DPP4i-BP and anti-BP230 Abs.